Assessing the product attributes of Iranian localized frozen dumpling dough incorporated with fish paste - M. Shirazy; N. Mooraki; M. Honarvar (Discover Food)
Abstract In this study, the properties of frozen dumpling dough produced by replacing 0% (Control), 10% (T1), and 20%(T2) of wheat flour with Hypophthalmichthys molitrix paste were evaluated through chemical, microbiological, and sensory tests. The dumplings were stored at – 18 °C for 3 months, and assessments were conducted in triplicate every 30 days. The pH, total ash, acid insoluble ash, and salt percentage did not significantly differ between the samples (P > 0.05); however, the samples' moisture, crude protein, crude lipid, peroxide, contents did significantly differ (P < 0.05). There was a noticeable variation (P < 0.05) in the overall counts of yeast and mold in the samples. Discriminant Analysis (DA) and Product Characterization analysis indicated that replacing 20% FP and storing for 90 days did not meet consumer demand. The chemical and sensory characteristics of dumplings stored at – 18 °C for 60 days post-production showed that wheat flour can be replaced with 10% silver carp paste.